A checklist of the snake fauna of Guinea, with taxonomic changes in the genera Philothamnus and Dipsadoboa (Colubridae) and a comparison with the snake fauna of some other West African countries - Trape, Jean-François; Baldé, Cellou (Zootaxa, 2014)
We present here the results of a study of 4,906 snakes from Guinea belonging to 95 species collected from 2002 to 2013 at 54 localities in all administrative regions of the country. We resurrect Dipsadoboa guineensis from the synonymy of D. brevirostris and consider the latter species a junior synonym of D. duchesnei. In addition we resurrrect Philothamnus pobeguini and P. belli from the synonymy of P. heterodermus. 19 species were not previously collected in this country, including Letheobia coecata, Tricheilostoma bicolor, Myriopholis rouxestevae, Rhinoleptus koniagui, Python regius, Grayia tholloni, Natriciteres fuliginoides, Philothamnus heterolepidotus, Thrasops aethiopissa, Amblyodipsas unicolor, Gonionotophis granti, Mehelya crossi, Prosymna gregeirti, Prosymna meleagris, Rhamphiophis oxyrhynchus, Elapsoidea trapei, Naja katiensis, Naja senegalensis and Echis jogeri. Based on a critical review of literature and our own data, we compare the currently known snake fauna of Guinea (104 species) with that of Sierra Leone (65 species), Liberia (63 species), Ivory Coast (101 species), Ghana (102 species), Togo (93 species), Benin (72 species) and Nigeria (118 species).